Natural cholinesterase inhibitors from Myristica cinnamomea King. Issue 15 (1st August 2016) - Abdul Wahab, Siti Mariam; Sivasothy, Yasodha; Liew, Sook Yee; Litaudon, Marc; Mohamad, Jamaludin; Awang, Khalijah
Graphical abstract: Abstract: A new acylphenol, malabaricone E (1 ) together with the known malabaricones A-C (2 –4 ), maingayones A and B (5 and6 ) and maingayic acid B (7 ) were isolated from the ethyl acetate extract of the fruits of Myristica cinnamomea King. Their structures were determined by 1D and 2D NMR techniques and LCMS-IT-TOF analysis. Compounds3 (1.84 ± 0.19 and 1.76 ± 0.21 μM, respectively) and4 (1.94 ± 0.27 and 2.80 ± 0.49 μM, respectively) were identified as dual inhibitors, with almost equal acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes inhibiting potentials. The Lineweaver–Burk plots of compounds3 and4 indicated that they were mixed-mode inhibitors. Based on the molecular docking studies, compounds3 and4 interacted with the peripheral anionic site (PAS), the catalytic triad and the oxyanion hole of the AChE. As for the BChE, while compound3 interacted with the PAS, the catalytic triad and the oxyanion hole, compound4 only interacted with the catalytic triad and the oxyanion hole.